Stack the Bowls: Tailoring the Electronic Structure of Corannulene‐Integrated Crystalline Materials. (30th July 2018) - Rice, Allison M.; Dolgopolova, Ekaterina A.; Yarbrough, Brandon J.; Leith, Gabrielle A.; Martin, Corey R.; Stephenson, Kenneth S.; Heugh, Rebecca A.; Brandt, Amy J.; Chen, Donna A.; Karakalos, Stavros G.; Smith, Mark D.; Hatzell, Kelsey B.; et al.
Abstract: We report the first examples of purely organic donor–acceptor materials with integrated π‐bowls (πBs) that combine not only crystallinity and high surface areas but also exhibit tunable electronic properties, resulting in a four‐orders‐of‐magnitude conductivity enhancement in comparison with the parent framework. In addition to the first report of alkyne–azide cycloaddition utilized for corannulene immobilization in the solid state, we also probed the charge transfer rate within the Marcus theory as a function of mutual πB orientation for the first time, as well as shed light on the density of states near the Fermi edge. These studies could foreshadow new avenues for πB utilization for the development of optoelectronic devices or a route for highly efficient porous electrodes.